Student’s opinion concerning a computer assisted introduction for the basic human needs teaching - Lopes, Marcos Venícios de Oliveira; Araújo, Thelma Leite de (Rev Rene, 2000)
Study of descriptive character that seeks to arise the students’ opinion about the use of a computer’s software as an instrument for Horta’s Basic Human Needs teaching (1979). The work was developed with 27 first semester students which are undertaking the Federal University of Ceará’s nursing graduation course in the period of 1998.2. The data were organized in categories and analyzed according to the convergence of the speeches. The results allowed us to arise some software’s aspects that were needing adjusts for a best acting. The student pointed the presence of ignored scientific terms, the necessity of working together with their teacher during the software use and they exalted the interactivity and freedom experienced in this theme study proportioned by the software use. We concluded that the software can be used as additional resource for the human basic needs teaching as soon as the suggested adjusts were made.